Evaluation of the implementation of governmental policies and actions to create healthy food environments in Burkina Faso - Viviane Aurélie Tapsoba; Ella WR Compaore; Augustin Nawidimbasba Zeba; Jerome Winbetourefa Some; Julien Soliba Manga; Adama Diouf; Jean-Claude Moubarac; Stefanie Vandevijvere; Mamoudou H Dicko (Public Health Nutrition, 2025)
Abstract